Age‐related changes of sulcal imprints on the endocranium in the Japanese macaque (Macaca fuscata). Issue 2 (16th March 2017) - Van Minh, Nguyen; Hamada, Yuzuru
Abstract: Objectives: The degree of expression of sulcal patterns on endocasts of nonhuman primates has been shown to depend primarily on species (brain size) and age of the individual. It has been suggested that brain details on endocasts are reproduced better in juvenile than adult primates. Here, we investigated age‐related changes in the imprint of the major sulci on the endocranium of Japanese macaques ( Macaca fuscata ) from the juvenile period to adulthood. Materials and methods: Using CT scans of 25 (12 males, 13 females) cranial specimens from macaques, we generated virtual endocasts to assess imprints of the seven main sulci on the endocranial surface. Expression of each sulcal imprint was evaluated by imprint score method. Results: The degree of expression of sulcal imprints differed between sulci. Arcuate, superior temporal, and principal sulci were well defined, whereas lunate and intraparietal sulci were poorly represented. Sulcal imprints showed significant age‐related changes in Japanese macaques from juvenile to elderly. Sulcal imprints showed a slight decrease in degree of expression from the juvenile period (2–4 years) to adolescence (4–6 years), and then remained unchanged until mid‐adulthood (15–16 years). The degree of expression of the sulcal imprints significantly decreased from mid‐adulthood to old age (>20 years). Conclusions: The degree of expression of the sulcal imprints (relief forms) in inner table bone surface (endocranium) reveals significant age‐related decreases in adults. The great decrease starts at around 20 years of age. The endocranial volume showed a significant age‐related increase, and thus, it is suggested that the endocranial surface in macaques may be resorbed with advancing age.